ChemInform Abstract: Significance of Microwave‐Assisted Technique in Green Chemistry. Issue 8 (1st March 2013) - Charde, M.; Shukla, A.; Bukhariya, V.; Mehta, J.; Chakole, R.
Abstract Review: 26 refs.